PENILAIAN KEBERHASILAN PROGRAM TB DOTS BERDASARKAN ANGKA KEBERHASILAN PENGOBATAN DAN ANGKA KONVERSI DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2008 – DESEMBER 2012 - Nyta Hasra M; Azizman Saad; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
World Health Organization (WHO) classified tuberculosis (TB) as global emergency at the end of 1993. Directly Observed Treatment Short-course (DOTS) is a direct supervision for short-term treatment, recommended by the World Health Organization for the world TB prevention. The Millennium Development Goals (MDGS) in 2015 is to reduce the number of deaths caused by tuberculosis for 50%. To achieve the target, program policy against tuberculosis improvement and evaluation will be needed. Evaluation in this research done by using two nasional indicators, which are success rate (national targets should be at least 85%) and conversion rate (national targets should be at least 80%). This research was using mixed methods with quantitative and qualitative approachment. Samples was taken by total sampling method, where 304 people have obtained as quantitative research samples and 3 people as qualitative research samples. Research results showed that the success rate at the end of 2009 and 2012 was 94%, in 2010 was 93%, in 2011 was 86%, and in 2008 was 77%. While the conversion rate at the end of 2011 was 96%, in 2012 was 94%, in 2009 was 91%, in 2008 was 89%, and in 2010 was 82%. It can be concluded that success rate in General Hospital Arifin Achmad Riau Province in 2008 have not reached national targets yet, but in 2009, 2010, 2011, and 2012 have exceeded national targets. The conversion in General Hospital Arifin Achmad Riau Province at the end of 2008, 2009, 2010, 2011 and in 2012 have exceeded national targets.Key words : Tuberculosis (TB), Directly Observed Treatment Short-course (DOTS), success rate, conversion rate